Surface Engineering for Extremely Enhanced Charge Separation and Photocatalytic Hydrogen Evolution on g‐C3N4. Issue 9 (15th January 2018) - Yu, Yu; Yan, Wei; Wang, Xiaofang; Li, Pei; Gao, Wenyu; Zou, Haihan; Wu, Songmei; Ding, Kejian
Abstract: Reinforcing the carrier separation is the key issue to maximize the photocatalytic hydrogen evolution (PHE) efficiency of graphitic carbon nitride (g‐C3 N4 ). By a surface engineering of gradual doping of graphited carbon rings within g‐C3 N4, suitable energy band structures and built‐in electric fields are established. Photoinduced electrons and holes are impelled into diverse directions, leading to a 21‐fold improvement in the PHE rate. Abstract : A facile surface engineering strategy of gradual doping of Cgra rings at different depths to surface in g‐C3 N4 is presented. Suitable energy band layouts and built‐in electric fields drastically accelerate carrier separation by impelling photoinduced electrons and holes into diverse directions, and hence elevate the photocatalytic hydrogen evolution rate by 21‐fold.